2019
DOI: 10.1371/journal.pntd.0007849
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy combined with antifungal drugs against chromoblastomycosis and the effect of ALA-PDT on Fonsecaea in vitro

Abstract: BackgroundChromoblastomycosis is a chronic skin and subcutaneous fungal infection caused by dematiaceous fungi and is associated with low cure and high relapse rates. In southern China, Fonsecaea monophora and Fonsecaea pedrosoi are the main causative agents.Principal findingsWe treated 5 refractory and complex cases of chromoblastomycosis with 5-aminolevulinic acid photodynamic therapy (ALA-PDT) combined with oral antifungal drugs. The lesions improved after 4 to 9 sessions of ALA-PDT treatment at an interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…Our limited experience in our service obtained cure and/or clinical improvement in 7 out 10 cases treated. Several authors have shown that cryotherapy and photodynamic therapy appear promising as adjunctive therapy in patients with extensive lesions [ 39 , 40 ]. Recently, some Brazilian groups, including our center, have been using topical immunomodulatory drugs (imiquimod) or intramuscular administration of glucan as adjuvant therapy, obtaining significant improvement of the lesions, but without cure [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our limited experience in our service obtained cure and/or clinical improvement in 7 out 10 cases treated. Several authors have shown that cryotherapy and photodynamic therapy appear promising as adjunctive therapy in patients with extensive lesions [ 39 , 40 ]. Recently, some Brazilian groups, including our center, have been using topical immunomodulatory drugs (imiquimod) or intramuscular administration of glucan as adjuvant therapy, obtaining significant improvement of the lesions, but without cure [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination of antifungal drugs and PDT may enhance the penetrability of photosensitiser due to the increase of the permeability of fungal cell membrane, so as to make them have synergistic killing effect. 19 In conclusion, we reported a case of chromoblastomycosis due to F monophora, presenting unusual clinical manifestations. We described in detail the necessary diagnostic procedures and summarised the characteristics of laser, photodynamic therapy and retinoic acid treatment for CBM in the literature.…”
Section: Re Vie W and Discussionmentioning
confidence: 75%
“…Hence, CO 2 laser can not only play a therapeutic role, but also improve the efficacy of photodynamic therapy. Moreover, the combination of antifungal drugs and PDT may enhance the penetrability of photosensitiser due to the increase of the permeability of fungal cell membrane, so as to make them have synergistic killing effect 19 …”
Section: Review and Discussionmentioning
confidence: 99%
“…Combining the potential of PDT with antibiotics in treating bacterial infections [16], the approach could also be applied to other infectious ulcers. Furthermore, it has been reported that miconazole can be used to increase the efficacy of PDT against Candida albicans [17] and antifungal agents combined with ALA-PDT can enhance the treatment of chromoblastomycosis [18]. Given those results, we hypothesized that PDT might also increase the efficacy of itraconazole against trichosporonosis.…”
Section: Discussionmentioning
confidence: 93%